The Effect of social capital on integrated pest management technology adoption - Amek, Tom (KDI School, 2011)
Agriculture plays a pivotal role in Kenya’s economic growth and development. As the sector becomes less productive, the entire economy suffers and poverty levels among the rural population worsen. Of serious concern is that pests largely contribute to the decline in agricultural productivity as they destroy up to half of all crops in the rural farms. Highly toxic chemical pesticides can reverse this loss but the cost and negative effects on health and on the environment are enormous. Integrated Pest Management (IPM) is recommended as it lowers the production cost, has no health and environmental hazards, and improves the long term sustainability of farming in the rural areas. A better understanding of IPM adoption process is therefore important. One element that is hypothesized to have a demeanor on IPM adoption is social capital which is interpreted as the degree of association, the level of trust and networks within a community. Using a Tobit model, the study sets out to verify the hypothesis that social capital influences IPM adoption. The results of the Tobit estimates suggest that social capital variables significantly and positively influencing IPM adoption include a number of groups a household subscribes to; monetary contribution to groups; and informal chats with neighbors and group members.
Thesis(Master) --KDI School:Master of Public Policy,2011